2003
DOI: 10.1038/sj.gt.3302002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial virus phi29 pRNA as a hammerhead ribozyme escort to destroy hepatitis B virus

Abstract: The DNA-packaging pRNA of bacterial virus phi29, which forms dimers and then hexamers, contains two independent tightly self-folded domains. Circularly permuted pRNAs were constructed without impacting pRNA folding. Connecting the pRNA 5 0 /3 0 ends with variable sequences did not disturb its folding and function. These unique features, which help prevent two common problems -exonuclease degradation and misfolding in the cell, make pRNA an ideal vector to carry therapeutic RNAs. A pRNA-based vector was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 47 publications
(61 reference statements)
1
119
0
Order By: Relevance
“…16,21,22 In this study, a chimeric pRNA/siRNA targeting firefly or renilla luciferase was constructed, and the silencing efficiency was tested by transient transfection. The chimeric siRNA construct suppressed its target gene specifically and efficiently as demonstrated by a Dual reporter assay, in which the expression To determine whether the knockdown effects shown above were siRNA-specific, chimeric pRNA/siRNA monomers or dimers were treated with cell lysate or recombinant purified Dicer ( Figure 5), which is known for its unique function in processing long doublestranded RNA into 22-bp siRNA.…”
Section: Binding Of Folate-prna To Nasopharyngeal Carcinoma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,21,22 In this study, a chimeric pRNA/siRNA targeting firefly or renilla luciferase was constructed, and the silencing efficiency was tested by transient transfection. The chimeric siRNA construct suppressed its target gene specifically and efficiently as demonstrated by a Dual reporter assay, in which the expression To determine whether the knockdown effects shown above were siRNA-specific, chimeric pRNA/siRNA monomers or dimers were treated with cell lysate or recombinant purified Dicer ( Figure 5), which is known for its unique function in processing long doublestranded RNA into 22-bp siRNA.…”
Section: Binding Of Folate-prna To Nasopharyngeal Carcinoma Cellsmentioning
confidence: 99%
“…14 Therefore, the 5 0 /3 0 proximate double-stranded helical region 15 of pRNA can be redesigned to carry additional sequences without altering its secondary structure or intermolecular interactions. 16,17 Being a poorly differentiated carcinoma of the human upper respiratory tract, nasopharyngeal carcinoma has human folate receptors (hFR) that are highly expressed in epidermal carcinoma (KB) cells. Endocytosis of the ligand/receptor complex mediated by the binding of folate to hFR has been well studied, and macromolecules conjugated to folate have been successfully recognized by folate receptors and internalized into cells.…”
mentioning
confidence: 99%
“…The unique features uncovered from the studies of phi29 pRNA include (1) independent folding of the ATPase gp16 interaction domain (Lee and Guo 2006) and the motor binding domain (Reid et al 1994a,b,c;Zhang et al 1994Zhang et al , 1995b and (2) the capacity to harbor and escort therapeutic functional modules without causing misfolding or loss of function of the incorporated functionalities. These special properties of phi29 pRNA have led to the development of this RNA as a novel vehicle for applications in nanotechnology and medicine (Hoeprich et al 2003;Guo et al 2005aGuo et al , 2006Guo et al , 2012aKhaled et al 2005;Guo 2010;Abdelmawla et al 2011;Shu et al 2011a,b,c;Shukla et al 2011;Zhou et al 2011). Recently, it was found that the core structure of phi29 pRNA, a 54-nt three-way junction (3WJ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The 71/75 end has been shown to be located in a tightly folded area, 16 which buries and protects the ends from exonuclease degradation. 7 The chimeric pRNA building block with this aptamer also contained the appropriate right and left loops required for the engineering and fabrication of the trimeric complex.…”
Section: Engineering Of Chimeric Rna As Building Blocks For the Fabrimentioning
confidence: 99%
“…Additional functional RNA, such as a hammerhead ribozyme, have been conjugated to the double-stranded domain, resulting in enhanced cleavage efficiency of ribozyme. 7 Extensive studies reveal that siRNA is a double-stranded RNA helix.2 -5 ,28 To test whether it is possible to replace the pRNA helical region with double-stranded siRNA and to determine which construct has the optimal function in gene silencing and trimer formation, we constructed several chimeric pRNA/siRNA and their ability in gene silencing was tested. A 29-bp siRNA was connected to nucleotides 29/91 or 18/99 of pRNA, resulting in pRNA/siRNA(GFP)-29/91 and pRNA/siRNA(GFP)21/99, respectively.…”
Section: Determination Of the Length Requirement Of The Prna Vector Fmentioning
confidence: 99%